TANGGUNG JAWAB PELAKU TINDAK PIDANA PROSTITUSI MELALUI MEDIA ONLINE - Shalahudin Serba Bagus; M. Fariz Wahyu Pratama (universitas islam darul ulum lamongan, 2017)
Cybercrime is one of the forms or dimensions of contemporary evil that is one of the dark sides of technological advancement. One form of crime in the field of Cybercrime is the criminal act of online prostitution. The purpose of this study is to find out whether prostitution through online media is a criminal act and how the criminal liability to the perpetrators of prostitution crime through online media based on positive law in Indonesia with the decision of Pangkalpinang District Court number 267 / Pid.B / 2015 / PN. Pg. The research conducted in this journal is normative law research, this research uses the approach of legislation as well as the case approach. The result of the research is known that prostitution through online media is an act of criminal and criminal liability of the perpetrators of prostitution through online media found in the Book Criminal Law (Penal Code), Law Number 11 Year 2008 on Information and Electronic Transactions and Law Number 44 Year 2008 regarding Pornography.